'Learning to shape life' - a qualitative study on the challenges posed by a diagnosis of diabetes mellitus type 2 - Astrid Fink; Eva-Maria Fach; Sara Lena Schröder (BMC, 2019)
Abstract Background Diabetes mellitus type 2 is a central challenge for health policy and healthcare in all advanced countries. For the affected persons, living with a diagnosis of type 2 diabetes is difficult because the disease and its treatment have a considerable effect on daily life. The aim of this study was to investigate the challenges associated with a diagnosis of type 2 diabetes for those affected and the range, depth and complexities of the subjective perspectives of the patients under the conditions of the German healthcare system. Methods A cross-sectional qualitative study was conducted using a sample of 19 adult patients with type 2 diabetes mellitus. Patients were recruited successively from two specialized diabetological practices, three general practitioner's offices, and two hospitals. The patients were interviewed once in person using semi-structured interviews. All interviews were recorded, transcribed, and analysed based on grounded theory. Results Persons affected by diabetes mellitus type 2 seem to feel responsible for managing their disease. Two strategies of action could be identified: 1) patients strictly followed the recommendations of the physicians, or 2) they showed that they are knowledgably managing their diabetes mellitus type 2. The action strategy to address the disease seemed to be influenced by patients' confidence in themselves, the effectiveness of the interventions, or the patients' locus of control. Minor differences in educational status could be discovered, and patients who were less educated tended to follow the recommendations of the physicians very strictly and seemed to place more emphasis on being compliant, which goes hand in hand with a life with prohibitions and restrictions. In contrast, being perceived as competent patients who make their own rules to manage the disease in daily life appeared to be more important for people with higher education levels. Conclusion Patient education and self-management programmes for diabetes mellitus type 2 should take different types of learners into account. Giving less-educated patients specific recommendations for successful diabetes self-management is particularly important. Trial registration German clinical trial register (DRKS-ID: DRKS00007847).